Preparation of ferric phosphonate/phosphinate and their special action on flame retardancy of epoxy resin. Issue 25 (7th March 2018) - Huang, Yawen; Yang, Yu; Ma, Jiajun; Yang, Junxiao
ABSTRACT: Fe‐ and P‐based compounds have demonstrated promising performance in enhancing flame retardancy of epoxy resins. In this context, this work focuses on the preparation of new Fe/P hybridized nanomaterials and their effect on flame retardancy of epoxy resins. The Fe/P hybrids were facilely prepared via forming ferric phosphinates and phosphonates using hydrothermal reaction. Attractively, ferric phosphinates and phosphonates exhibit the morphology of 1D nanorod and 2D nanosheet, respectively. When incorporating these two fillers in epoxy resin, the limiting oxygen index values of composites were enhanced to above 28 and the composites exhibited self‐extinguishing behavior, thus indicating greatly improved fire resistance. Further investigation revealed that the flame retarding behavior, in particular for ferric phosphonate nanosheets, took place mainly in gas phases via delaying the release of flammable gas. Attractively, it was found that the Fe/P hybrids took part into the pyrolysis reaction of epoxy resins through forming FeO and PO bonds. This finding may provide a new insight to design a series of high performance flame retardants for epoxy resins. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46206. Abstract :